Biological activities of aerial parts extracts of endemic Tanacetum argenteum subsp. argenteum - ŞEN, ALİ; BİTİŞ, LEYLA; BİNGÖL ÖZAKPINAR, ÖZLEM (MARMARA UNIV, FAC PHARMACY, 2017)
The objective of the present study was to investigate the antimicrobial and anti-proliferative activities of n-hexane, chloroform, methanol and aqueous methanol extracts obtained from Tanacetum argenteum subsp. argenteum aerial parts. Anti-proliferative activity was tested in vitro against four human cancer cell lines (A549: lung adenocarcinoma, Hela; cervix adenocarcinoma, HT-29: colon adenocarcinoma, MCF-7; breast adenocarcinoma) using MTT assay. Antimicrobial activity was assessed by micro-broth dilution technique against Staphylococcus aureus ATCC 29213, Staphylococcus epidermidis ATCC 12228, Escherichia coli ATCC 25922, Enterococcus faecalis ATCC 29212, Klebsiella pneumoniae ATCC 4352, Pseudomonas aeruginosa ATCC 27853, Proteus mirabilis ATCC 14153, and Candida albicans ATCC 10231. Hexane extract inhibited proliferation of HT-29 and MCF-7 by 75 and 74% while chloroform extract against the same cancer cell lines displayed inhibition of 89 and 73% at the concentration of 30 mu g/mL, respectively. Also, chloroform extract at the same concentration showed significant anti-proliferative activity against A-549 and HeLa with inhibition values of 75% and 62%. Chloroform extract exhibited moderate antibacterial activity against Staphylococcus aureus and S. epidermidis with the MIC values of 625 mu g/mL. Methanol and aqueous methanol extracts showed weak antimicrobial activity against Staphylococcus epidermidis and Candida albicans with MIC values of 1250 mu g/mL. The results showed that n-hexane and chloroform extracts have significant anticancer activity against cancer cell lines used in this study.
Keywords: Asteraceae; antimicrobial activity; anti-proliferative activity; n-hexane extract; chloroform extract; ANTIOXIDANT ACTIVITIES; ANTIMICROBIAL ACTIVITY; ESSENTIAL OIL; FLABELLIFOLIUM; FLAVONOIDS; PLANTS; CELLS